Treffinger Learning to Enhance Statistical Literacy Primary Student - Nur Rohmah Emilia; Mohammad Faizal Amir (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2022)
Statistical literacy is a primary need for primary students as to skills in interpreting statistical data, and analyzing and solving statistical problems in the 21st century. However, statistical literacy for primary students is still inadequate. Moreover, there is still a lack of treffinger learning literature on statistical literacy for primary students. The aims of this study are to analyses the effect of treffinger learning on enhancing the statistical literacy of primary students. This study is quantitative study employs an experimental method and a pretest-posttest control group design. The subjects of this study are involving 40 students of class VI primary schools which divided into two groups. The experimental group is a class that follows mathematics learning using treffinger learning, while the control group is a class that uses conventional learning. SLT is use in determining statistical literacy level. The result of study found that overall average N-Gain results in both classes indicate achievement and enhancing statistical literacy through differences in SLS on medium criteria (0.3 ≤ g ≤ 0.7). When conducting the Wilcoxon test, it indicates 0.000 is less than the significance threshold of 0.05, so there is a difference in the average of the two classes, which means that the implementation of treffinger learning affects the statistical literacy of primary students. Hence, treffinger learning can enhance the statistical literacy of primary students.